Clinical Outcome Review: A Retrospective Assessment of 171 Patients Referred for Physiotherapy Treatment after Whiplash Injury by Medical Insurance Intermediaries - Berry, Gunnel (British Journal of Healthcare and Medical Research, 2025)
The purpose of this review is to share outcomes from 171 patients of acute and chronic grade 0-2 whiplash injury referred for physiotherapy treatment by nine insurance intermediaries after a road traffic accident. An unorthodox method of treatment and assessment was used and the review is retrospective. After assessment, a prediction of outcome including proposed method, number of treatments and improvement measured in percentages was delivered to the insurance intermediaries for approval prior to commencing treatment. In effect, the insurance intermediaries became external assessors in all cases with the author acting as the sole physiotherapist carrying out the assessment and treatment. Adapted Reflextherapy was used as the method to assess and treat all patients. Nine patients did not start or complete the treatment leaving 162 patients included in the review. The mean number of treatments per patient was 5.02. Pain levels varied between 0 and 10 on the VAS scale with 65% (106) of patients reporting pain levels between 5 and 10 before treatment, dropping to below 2 after treatment. In 41% (66), fewer treatments were required to achieve the expected outcome. In 30% of patients (48), the prediction of outcome was completely correct. 30% (52) of patients required a few more treatments than predicted requiring approval from the insurance companies.